Global and Interregion Characterization of Subduction Interface Earthquakes Derived From Source Time Functions Properties. Issue 7 (23rd July 2018) - Chounet, Agnès; Vallée, Martin
Abstract: Source time functions (STFs) describe how the seismic moment rate is released with time, and carry information on integral rupture properties, such as static stress drop and radiated energy. In this study, we systematically analyze a set of 1, 433 STFs extracted from the SCARDEC method (Vallée and Douet, 2016, https://doi.org/10.1016/j.pepi.2016.05.012 ), containing the M w ≥5.6, shallow ( z ≤70 km) earthquakes with dip‐slip mechanism that occurred between 1992 and 2014. At the global scale, STFs properties indicate scale invariance of stress drop and scaled radiated energy with magnitude. In a second step, these source parameters are investigated in light of the tectonic context of the earthquakes: in agreement with other approaches, we observe that subduction interface earthquakes have lower stress drop and scaled radiated energy relative to all other earthquakes (e.g., crustal earthquakes). Finally, a focus on subduction interface earthquakes (approximately 800 earthquakes) is done by considering 18 regional segments of subduction zones. We find that these segments do not have the same signature in terms of macroscopic rupture properties, which means that large‐scale plate convergence and mechanical properties influence rupture behavior. In a given segment, local heterogeneities of stress drop or radiated energy can be associated with local features of the subduction zone: in particular, we find that low coupled zones generate earthquakes with low stress drop and scaled radiated energy. This last feature, also observed at a larger scale, suggests a positive correlation between coupling and stress drop. Key Points: Dip‐slip earthquakes are characterized using the SCARDEC global database of source time functions Subduction interface earthquakes have systematically lower stress drops than other earthquakes A positive correlation is found between subduction earthquakes impulsivity and interface coupling